Incorporating Internet of Things Applications in Healthcare - Kumar, Basant; Ismaili, Majid Al (Current Overview on Science and Technology Research Vol. 1, 2022)
Internet of things applications in healthcare are an important field to learn about as many diseases and viruses are spreading these days, so with the spreading of viruses, we need to learn more about healthcare and the applications based on the internet of things that are connected to the healthcare. Many patients who are suffering from diseases need some applications to have a comfortable environment that allows them to ask for help easily, and we can list some applications like Implantable Glucose Monitoring systems, Activity Trackers During Cancer Treatment, Heart Monitors with reporting, Medical Alert Systems, Ingestible Sensors, wearables to Fight Systems Depression, Connected Contact Lenses, Location Services, Remote Monitoring.